1721d Outcome of the positive training programme for improving working conditions in india. (24th April 2018) - Nagasu, M; Yoshikawa, T; Katsumura, R; Wakatsuki, T; Jaganathan, VR; Sanjeeva Reddy, G; Kogi, K
Abstract : Introduction: In accordance with the International Labour Organisation's Global Strategy on Occupational Safety and Health, it is essential to develop practical training programmes for improving local working conditions in low- and middle-income countries. The Participation-Oriented Safety Improvements by Trade Union Initiative (POSITIVE) programme has involved many workers in developing countries in action-oriented workshops on multifaceted workplace improvements. The programme was introduced in India in collaboration with the Indian National Trade Union Congress (INTUC) and the Japan International Labour Foundation (JILAF). This study aimed to evaluate the effectiveness of the programme. Methods: The POSITIVE workshops were serially held for training trainers selected from trade union members in 13 engineering companies. Subsequently a training-of-trainers (TOT) workshop was conducted in November 2013, and after a re-training workshop of these trainers, the participants conducted a one-day workshop for their co-workers in their workplaces. An evaluation workshop was held in September, 2014. The results of these workshops and the implemented improvements were evaluated. Results: The POSITIVE workshops proved successful in India. In the TOT workshop, 25 participants from 13 factories learned practical ways to plan multifaceted improvements having real impact. The participants conducted a one-day workshop at 15 workplaces training 476 workers. Almost all of the participants answered that the technical sessions of the programme were useful for increasing knowledge and improving their working conditions. After this one-year programme, the participants reported 188 improvements implemented at their own workplaces. Discussion: The POSITIVE training programme was effective for workers in engineering industries to improve their working conditions by using their own ideas in reducing work-related risks. Practical training tools such as the action checklist, group discussion and local good-practice photos were useful for gaining these results. It is suggested that the POSITIVE programme for factory workers can play important roles in improving their workplace conditions.